Solar PV cell materials and technologies: Analyzing the recent developments. (2021) - Singh, Bhuwan Pratap; Goyal, Sunil Kumar; Kumar, Prakash
Abstract: In last five years, a remarkable development has been observed in the photovoltaic (PV) cell technology. To overcome the consequences on global warming due to fossil fuel-based power generation, PV cell technology came out as an emerging and sustainable source of energy. A renewed assessment regarding the performance of this emerging technology is essentially required for the recent developments and to analyze their potential in forthcoming applications. The developments of various PV cells can be classified in to four primary groups, known as generations. However, the first two generations are mainly responsible till date for the commercialization of solar PV cells in the entire market. The efforts have been made in this approach to appraise the progress of each technology in the near future by presenting a comprehensive comparative study of PV cell parameters for all generation technologies. Additionally, the fourth-generation technology has been especially focused in this work in which the distinct roles of organic and nano-components is presented.